A comparative review of deep and spiking neural networks for edge AI neuromorphic circuits - M. Ferreira, Pietro; Wang, Siqi; Gao, Yueyuan; Benlarbi-Delai, Aziz (Frontiers in Neuroscience, 2025)
Edge AI implements neural networks directly in electronic circuits, using either deep neural networks (DNNs) or neuromorphic spiking neural networks (SNNs). DNNs offer high accuracy and easy-to-use tools but are computationally intensive and consume significant power. SNNs utilize bio-inspired, event-driven architectures that can be significantly more energy-efficient, but they rely on less mature training tools. This review surveys digital and analog edge-AI implementations, outlining device architectures, neuron models, and trade-offs in energy (J/OP), area (μm2/OP), and integration technology.